2011
DOI: 10.1111/j.1463-5224.2011.00957.x
|View full text |Cite
|
Sign up to set email alerts
|

Feline calicivirus: a neglected cause of feline ocular surface infections?

Abstract: Results indicate that FCV is highly prevalent in cats with URTD either as a sole infectious agent or in combination with other pathogens and therefore is a potential cause for ocular surface lesions during the URTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 53 publications
(76 reference statements)
4
16
1
Order By: Relevance
“…In contrast to cats in short-term shelters, foster programs, or trap-neuterreturn programs, cats housed long-term in sanctuaries are more likely to be infected with FCV than FHV, similar to the findings of cats from the cases in this report (McManus et al, 2014). The high prevalence of FCV among cats with URI is concerning because of considerable strain variability in its pathogenicity, transmissibility, and environmental stability and its association with a wide array of clinical signs including fever, conjunctivitis, oral ulceration, limping, ocular and nasal discharge, and gingivostomatitis (Reubel et al, 1992;Dawson et al, 1994;Pedersen et al, 2000;Radford et al, 2007;Gerriets et al, 2012). The reason for the shift from high prevalence of FHV in cats in short-term shelter housing to high prevalence of FCV in cats in long-term group-housed confinement is unknown (Reubel et al, 1992;Lommer and Verstraete, 2003;Dowers et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…In contrast to cats in short-term shelters, foster programs, or trap-neuterreturn programs, cats housed long-term in sanctuaries are more likely to be infected with FCV than FHV, similar to the findings of cats from the cases in this report (McManus et al, 2014). The high prevalence of FCV among cats with URI is concerning because of considerable strain variability in its pathogenicity, transmissibility, and environmental stability and its association with a wide array of clinical signs including fever, conjunctivitis, oral ulceration, limping, ocular and nasal discharge, and gingivostomatitis (Reubel et al, 1992;Dawson et al, 1994;Pedersen et al, 2000;Radford et al, 2007;Gerriets et al, 2012). The reason for the shift from high prevalence of FHV in cats in short-term shelter housing to high prevalence of FCV in cats in long-term group-housed confinement is unknown (Reubel et al, 1992;Lommer and Verstraete, 2003;Dowers et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…In relation to FCV, it has traditionally been considered as a minor primary conjunctival pathogen (MOCHIZUKI et al, 2000;GERRIETS et al, 2012;BERGER et al, 2015). In the present study it was observed in the same proportion as FHV-1, both in G1 and G2, in different scores, and it is possible that its role has been neglected.…”
Section: Discussionsupporting
confidence: 51%
“…In some outbreaks of virulent systemic FCV, large percentages of cats have died (Hurley et al, 2004;Coyne et al, 2006;Reynolds et al, 2009) Feline calicivirus has been cited as causing only mild conjunctivitis (Ramsey, 2000). However, a recent study of 99 cats with URTD, as well as ocular surface disease, found that ocular samples analyzed using PCR were positive for FCV alone in 11 (11.1%) cats; in 19 (19.2%) cats, FCV was present with other infectious agents, including FHV-1 (Gerriets et al, 2012). Moderate to severe conjunctivitis with conjunctival epithelial erosions, as well as oral mucosal ulceration, were noted in FCV-positive cats.…”
Section: Clinical Signsmentioning
confidence: 96%